Sebaceous carcinoma of the forehead: Case report - Mehmet Eren Yuksel; Funda Tamer (Our Dermatology Online, 2016)
Sebaceous carcinoma is an uncommon malign tumor arising from sebaceous glands. Sebaceous carcinoma typically occurs on the eyelid as a slow growing, pink-yellow, painless subcutaneous papule or nodule. Although it is rare, sebaceous carcinoma can also be seen on head, neck, trunk, extremities, breasts, oral mucosa and external genitalia. Sebaceous carcinoma is a locally aggressive tumor, moreover it can metastasize to regional lymph nodes and distant organs. Hereby, we report a 91-year-old Caucasian female with sebaceous carcinoma on the forehead. The extraocular 1,9 cm large sebaceous carcinoma on the forehead was removed surgically with wide local excision under local anesthesia.